Nuremberg Principles as a Basis of International Criminal Justice - Сенаторова, О. В. (Theory and practice of jurisprudence, 2016)
This article is devoted to the evaluation of the significance of the Nuremberg Trial for the formation of the international criminal law and procedure as a branch of international law. The legal nature of the Tribunal is described, the criticism of the legality is analysed. The significance of the principles set out by the Nuremberg Charter and Judgment as a foundation of the unique architecture of international criminal justice is argued